Parental occupations at birth and risk of adult testicular germ cell tumors in offspring: a French nationwide case–control study - Paul, Adèle; Danjou, Aurélie M. N.; Deygas, Floriane; Guth, Margot; Coste, Astrid; Lefevre, Marie; Dananché, Brigitte; Kromhout, Hans; Spinosi, Johan; Béranger, Rémi; Pérol, Olivia; Boyle, Helen; et al. (Frontiers in Public Health, 2024)
Background Testicular germ cell tumors (TGCT) are the most frequent cancer in young men in developed countries. Parental occupational exposures during early-life periods are suspected to increase TGCT risk. The objective was to estimate the association between parental occupations at birth and adult TGCT. Methods A case–control study was conducted, including 454 TGCT cases aged 18–45 from 20 French university hospitals, matched to 670 controls based on region and year of birth. Data collected from participants included parental jobs at birth coded according to the International Standard Classification of Occupation—1968 and the French nomenclature of activities—1999. Odds ratios (OR) for TGCT and 95% confidence intervals (CI) were estimated using conditional logistic regression, adjusting for TGCT risk factors. Results Paternal jobs at birth as service workers (OR = 1.98, CI 1.18–3.30), protective service workers (OR = 2.40, CI 1.20–4.81), transport equipment operators (OR = 1.96, CI 1.14–3.37), specialized farmers (OR = 2.66, CI 1.03–6.90), and maternal jobs as secondary education teachers (OR = 2.27, CI 1.09–4.76) or in secondary education (OR = 2.35, CI 1.13–4.88) were significantly associated with adult TGCT. The risk of seminoma was increased for the above-mentioned paternal jobs and that of non-seminomas for public administration and defence; compulsory social security (OR = 1.99, CI 1.09–3.65); general, economic, and social administration (OR = 3.21, CI 1.23–8.39) for fathers; and secondary education teacher (OR = 4.67, CI 1.87–11.67) and secondary education (OR = 3.50, CI 1.36–9.01) for mothers. Conclusion Some paternal jobs, such as service workers, transport equipment operators, or specialized farmers, and maternal jobs in secondary education seem to be associated with an increased risk of TGCT with specific features depending on the histological type. These data allow hypotheses to be put forward for further studies as to the involvement of occupational exposures in the risk of developing TGCT, such as exposure to pesticides, solvents, or heavy metals.